Research report of the analysis on enterprises simulators MC Donalds and Ceme (2015)
This research report wants to analyze two different tycoons (Mc Donald’s and CEME), trying to identify if they cover the 4 most important areas of the enterprise (management, marketing, finances and human resources) also, look for the strengths and weaknesses they have as business simulators. For testing them, a group of 4 graduated Colombian students of business administration were chosen to play with both tycoons and then they help to solve a questionnaire answering about different features of the tycoons. In order to analyze the games, a matrix was created for a detailed analysis and to observe the specific characteristics of each one of the.